Gasdynamic Elements of Dispersive Medium - Ivanov, M. Ja.; Terentieva, L. V. (Gasdynamic Elements of Dispersive Medium, 2021)
Aspects of motion theory for gaseous continuous medium at essential influence of dispersion effects, related to the medium microstructure or presence of internal force fields of an electromagnetic or gravitational nature are presented. The exact stationary solutions of non-linear equations in vicinity of transition fronts and in the shape of solitary waves – “classical” and “particle-like” solitons are analyzed in details. Various gasdynamic models – starting with acoustic theory of relativity and supercritical analogue of the special theory of relativity up to model of the Newtonian dark matter and microstructural turbulence are demonstrated. Common conformities of investigated processes by a number of examples taken from gas dynamics and physics are illustrated.